Experimental Evidence on Forecaster (anti-) Herding in Sports Markets - Christoph Bühren; Tim Meyer; Christian Pierdzioch (Philipps-University Marburg, School of Business and Economics, 2020)
We experimentally analyzed whether (anti-)herding behavior of forecasters in sport-betting markets is influenced by the incentive structure of the market (winner-takes-all vs. equal payment of most accurate forecasts) and by personal traits of forecasters. We found evidence of anti-herding in forecasts of the German Bundesliga. Self-reported knowledge and, more surprisingly, winner-takes-all incentives reduced anti-herding. On average, forecasts were less accurate with stronger anti-herding. Winner-takes-all incentives and self-reported knowledge improved forecasts.
Keywords: 330; (Anti-)Herding; Sports forecasting; Experiment; Survey data